'11 for Health', a football-based health education programme for children: a two-cohort study in Mauritius and Zimbabwe. Issue 8 (19th April 2011) - Fuller, Colin W; Junge, Astrid; Dorasami, Cadrivel; DeCelles, Jeff; Dvorak, Jiri
Abstract : Objectives: To implement and assess Fédération Internationale de Football Association Medical Assessment and Research Centre's '11 for Health' football-based health education programme for children. Design: Prospective, 2-cohort study. Setting: In-school groups (Mauritius); out-of-school groups (Zimbabwe). Participants: Mauritius: 389 children, aged 12–15 years; Zimbabwe: 395 children, aged 10–14 years. Intervention: Eleven 90-min sessions, each divided into two 45-min halves of Play Football (focusing on one football skill) and Play Fair (focusing on one health issue). Main outcome measures: 30-item questionnaire implemented pre and postintervention to assess children's health knowledge; six-item questionnaire implemented postintervention to assess children's views about the '11 for Health' programme. Results: Mean pre and postintervention health knowledge scores were greater in Mauritius (pre: 69.3%; post: 87.1%) than Zimbabwe (pre: 57.8%; post: 76.2%) but the mean gain in health knowledge was greater in Zimbabwe (18.4%) than Mauritius (17.8%). There were few significant differences in the outcomes for boys and girls in both countries. The '11 for Health' programme was received positively by the children in both countries and there were no significant differences in the views of boys and girls in either country. Conclusions: The study demonstrated that it was possible to achieve significant increases in children's knowledge for all health messages by implementing the '11 for Health' programme in a school-based setting in collaboration with a national Football Association and in an out-of-school setting in collaboration with a non-government organisation. Based on these positive results, the authors recommend that the programme be widely implemented in Africa in co-operation with government and non-government organisations.